Changes in Chemical Composition of Camel’s Raw Milk During Storage - Haroun Omer, Rea Haroun; Eltinay, Abdullah Hamid (Pakistan Journal of Nutrition, 2009)
A total of 70 samples of individual dromedary raw milks were collected from different areas in UAE. The milk samples were divided into three portions under sterile conditions the 1st portion stored at 4oC, the 2nd portion stored at 7oC, the 3rd portion stored at room temperature (25-30oC). Samples were examined for pH, acidity, fat, protein, lactose, total solids and ash contents. The results shows that there were significant changes in pH, acidity, lactose, total solids and insignificant changed in fat, protein, during storage. The storage duration of raw camel milk was estimated at 4oC, 7oC and room temperature (25-30oC), the results was 42 days at 4oC, 15 days at 7oC, 3 days, at room temperature.